Credit Conditions in Pakistan: Supply Constraints or Demand Deficiencies?. (June 2016) - Ahmed, Jameel
Abstract : This paper attempts to pin down the key drivers of demand for and supply of real private sector credit in Pakistan. I use both the equilibrium and disequilibrium econometric frameworks, specifically tackling the issue of lack of consistency and/or efficiency of joint estimators in the former via the three‐stage least squares technique. On the demand side, I find that higher economic activity provides stimulus to credit whereas inflation dampens it. The stock market seems to play a dual role: as a source of alternative financing, a bullish market negatively impacts credit while, as an indicator of economic expectations, it provides a positive impetus. On the supply side, banks' lending capacity is found to be the major driver of credit while government borrowing has a crowding‐out effect. Pakistan currently faces supply constraints, which might put an additional check on capacity utilization by firms, thus damaging growth prospects. The results have important policy implications.